The value of myocardial work in the estimation of left ventricular systolic function in patients with coronary microvascular disease: A study based on adenosine stress echocardiography - Liu, Quande; Li, Qimou; Wan, Xiaoyu; Xu, Mingjun; Pan, Jichen; Zhang, Yu; Li, Mengmeng; Zhang, Mei (Frontiers in Cardiovascular Medicine, 2023)
Background Coronary microvascular dysfunction (CMD) is associated with increased cardiovascular events in patients with angina with non-obstructive coronary (ANOCA), especially heart failure. Conventional echocardiography is difficult to identify early alterations in cardiac function due to CMD. Methods We recruited 78 ANOCA patients. All patients underwent conventional echocardiography examination, adenosine stress echocardiography and examination of coronary flow reserve (CFR) by transthoracic echocardiography. Based on the CFR results, patients were divided into the CMD group (CFR < 2.5) and the non-CMD group (CFVR ≥ 2.5). Demographic data, conventional echocardiographic parameters, two-dimensional speckle-tracking echocardiography (2D-STE) parameters and myocardial work (MW) were compared between the two groups at rest and at stress. Logistic regression was used to analyze the factors associated with CMD. Results There was no significant difference in conventional echocardiography parameters, 2D-STE related indices or MW at rest between the two groups. Global work index (GWI), global contractive work (GCW), and global work efficiency (GWE) were lower in the CMD group than in the non-CMD group at stress (p = 0.040, 0.044, <0.001, respectively), but global waste work (GWW) and peak strain dispersion (PSD) were higher (both p < 0.001). GWI and GCW were associated with systolic blood pressure, diastolic blood pressure, product of heart rate and blood pressure, GLS and coronary flow velocity. While GWW was mainly correlated with PSD, GWE was correlated with PSD and GLS. In the non-CMD group, the responses to adenosine was mainly manifested as an increase in GWI, GCW and GWE (p = 0.001, 0.001, 0.009, respectively) and a decrease in PSD and GWW (p = 0.001, 0.015, respectively). In the CMD group, the response to adenosine was mainly manifested as an increase in GWW and a decrease in GWE (p = 0.002, and 0.006, respectively). In the multivariate regression analysis, we found that ΔGWW (difference in GWW before vs. after adenosine stress) and ΔPSD (difference in PSD before vs. after adenosine stress) were independent factors associated with CMD. The ROC curves showed that the composite prediction model consisting of ΔGWW and ΔPSD had excellent diagnostic value for CMD (area under the curve = 0.913). Conclusion In the present study, we found that CMD caused deterioration of myocardial work in ANOCA patients under adenosine stress, and that increased cardiac contraction asynchrony and wasted work may be the main changes caused by CMD.